A novel application of hectorite nanoclay for preparation of colorectal cancer spheroids with malignant potential. Issue 4 (12th January 2023) - Hirade, Yoshihiro; Kubota, Munehiro; Kitae, Kaori; Yamamoto, Harumi; Omori, Hiroko; Shinoki, Susumu; Ohmura, Takao; Tsujikawa, Kazutake
Abstract : A novel culture system where cancer cells are grown in the presence of nanoclay in adherent plates allows preparation of malignant and dispersed spheroids compared with those formed under ultralow-adherent conditions. Abstract : Three-dimensional (3D) cell culture, which provides an in vivo -like environment in vitro unlike the conventional two-dimensional (2D) cell culture, has attracted much attention from researchers. Although various 3D cell culture methods have been developed, information on a method using inorganic nanoclay is scant. Here, we report that hectorite, an inorganic layered silicate, can be used as an auxiliary material for 3D cell culture. Human colon cancer cell lines cultured in a medium containing 0.01% synthetic hectorite spontaneously formed 3D spheroids in an adherent plate. Morphologically, these spheroids were more dispersed in all directions than control spheroids generated in an ultralow adherent plate. Microarray analysis showed that FGF19, TGM2, and SERPINA3, whose expression is reportedly increased in colon cancer tissues and is related to tumorigenesis or metastasis, were upregulated in HT-29 spheroids formed using synthetic hectorite compared with those in control spheroids. Gene ontology analysis revealed upregulation of genes associated with morphogenesis, cytoskeleton, extracellular matrix, cellular uptake and secretion, signaling pathways, and gene expression regulation. Moreover, fluorescence-labeled hectorite particles were localized in the cytoplasm of individual cells in spheroids. These results suggest that the synthetic hectorite modified the physiological state of and gene expression within the cells, triggering spheroid formation with malignant characteristics. Our findings highlight a novel application of synthetic hectorite for 3D cell culture.